(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2025)
Background: Achilles tendinitis is a common overuse injury in marathon runners, particularly affecting females due to anatomical and hormonal factors. The long-distance and high-impact nature of marathon running places significant strain on the Achilles tendon, leading to inflammation and pain that can disrupt performance and training. Common interventions include exercise-based rehabilitation, which strengthens the muscles and tendons around the Achilles, and electrotherapy modalities like TENS and ultrasound therapy, which aim to enhance healing and reduce inflammation. Methodology: A comprehensive literature study was done using the specified search criteria to carry out a literature review, the search phrases "a review of female marathon runners with Achilles tendinitis to find out the effectiveness of exercise and electro-therapy" were employed between the years 2013 and 2024. We have discovered 14 publications with complete text and methodologies for additional examination from diverse academic journals. Results: Results indicate that a combination of targeted exercise programs and electrotherapy modalities (such as ultrasound and electrical stimulation) significantly reduced pain, improved functionality, and promoted faster recovery. The findings suggest that both treatments are beneficial when tailored to the specific needs of female marathon runners suffering from Achilles tendinitis Conclusion: We discovered 14 publications that had a review of female marathon runners with Achilles tendinitis to find out the effectiveness of exercise and electro-therapy for all individuals. All articles designed for his review emphasize the importance of a multidisciplinary approach and individualized care in optimizing patient outcomes for those with Achilles tendinitis.